(Re)viewing Cannibal Tours: lost in translation. (1st January 2012) - Burns, Peter; Zafiri, Konstantina
The film Cannibal Tours powerfully portrays the impact of tourism in the Sepik region of Papua New Guinea through an array of host-guest encounters. Using text from the film as data, the present paper reveals new insights through a close analysis of the English subtitles given as translation for the Italian and German tourists. The subtitles are examined at three levels of equivalence to establish translation strategy and impact. The whole text is also be submitted to analysis using the critical discourse analysis (CDA) method. The findings have far-reaching implications on several levels. First, they are insightful for the study of tourism in developing destinations. Second, they confirm the significance of using visual data for research in the social sciences. Third, they demonstrate that translation in films can impact heavily on film meaning-making and viewer perception.